CMLHS promotes Care to Share - Husna, Hashim (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
3 October 2010. University students play an important role in augmenting positive changes in society. Therefore, they need to be exposed to the reality and the actual needs of the society and for that, strengthening their personality and thoughtfulness will result in moulding good citizens.